A Comparative Study of the Ability of Facial Emotional Expression Recognition and its Relationship with Communication Skills in Iranian Patients with Mood Disorders: - Seyednezhad Golkhatmi, Seyed Hamid; Homayoni, Samaneh; Bakhshani, Nour Mohammad; Sadjadi, SeyedAlireza; Saidian Asl, Mohsen (Galen Medical Journal, 2015)
Background: Facial emotion recognition impairment in psychiatric patients such as those with mood disorders and impaired communication skills in these patients is one of the most important issues. The present study aims to evaluate and compare facial emotion recognition among patients with depression, bipolar disorder who experience manic phase and the subjects of the normal group without a diagnosis of a disorder. Moreover, the present study aims to evaluate and compare the relationship between facial emotion recognition ability and communication skills among these patients. Materials and Methods: Participants of this study included 30 patients with depression, 30 patients with bipolar disorder and 30 subjects from a normal group; a total of 90 subjects who were selected using convenience sampling method. PC version of Ekman’s facial emotion test (1976) and Queendom’s interpersonal communication skills test (2004) were used to collect data. Data were analyzed using statistical tests of correlation, one way analysis of variance and Tukey’s post hoc test. Results: The findings showed that there was a significant difference between facial emotion recognition in patients with mood disorder and the normal group. Moreover, there was a correlation between facial emotion recognition and communication skills among these patients. Conclusions: Based on the results of this study on facial emotion recognition impairment and its significant relationship with communication skills in patients with mood disorder, it can be said that paying attention to them is very important in treating these disorders and reducing the relapse of the disease.[GMJ. 2015;4(3):90-99]